Comparing traditional surveys and web-scraped data to understand the pigeon racing industry in Southern California - Pitesky, Maurice; Isa, Malekah; Rivera, Charlene; Streba, Elise; Gendreau, Joseph D. (Frontiers in Veterinary Science, 2025)
Recent outbreaks of virulent Newcastle disease (vND) in domestic poultry in Southern California have raised questions as to the source(s) and the mode(s) of transmission. While pigeons have been found to be capable of transmitting a variant of Newcastle disease virus (NDV) known as Pigeon paramyxovirus-1 (PPMV-1) to other avian species including poultry, the potential geographic distribution and scope of transmission from racing pigeons to other domestic poultry in Southern California is poorly understood. In order to better understand the potential risk of transmission of vND from racing pigeons to domestic poultry, an extension-initiated survey was conducted in addition to social-media based analysis of racing pigeon activity associated with postings on a web-based popular classified advertisement (CAW) in Southern California. Likely due to the insularity of the pigeon racing industry in Southern California, only 1 survey response was completed. However, monitoring results from the CAW demonstrated a much higher level of social media activity associated with racing pigeon sales in Southern California. Specifically, 191 unique posts associated with pigeon sales were flagged between 12/21/2020 and 1/21/2021 demonstrating the potential for the analysis of social media as an extension-based tool. Data from the CAW showed that the majority of pigeon related posts and sales came from both the Inland Empire region of Southern California and San Diego county which overlapped with the established vND control zone. From an extension perspective, while traditional-based surveys can still provide valuable information, web-scraping of social media can provide a continuous source of spatio-temporal data that can facilitate extension-based observations and analysis among hard to reach stakeholder groups.